Polyglycolide graft copolymer as well as preparation method and application thereof

Through the graft copolymerization reaction of maleic anhydride and glycolide, combined with low-temperature prepolymerization and high-temperature polymerization technology, the problem of insufficient heat resistance and toughness of polyglycolide materials is solved, and high-performance maleic anhydride grafted poly Glycolide copolymer, suitable for a variety of medical and engineering applications.

CN119264391AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310813496.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Polyglycolide materials have poor heat resistance and low toughness, making them difficult to be used in industrial use. The existing modification methods cannot fundamentally improve their thermodynamic properties. Moreover, the quality requirements of glycolide monomers are high, and the content of free hydroxyl groups affects the degree of polymerization.

Method used

Maleic anhydride and glycolide are used for graft copolymerization, and high-temperature polymerization is carried out by diapropyl peroxide as an initiator. Combined with twin-screw extruder technology, high-molecular-weight maleic anhydride joint is prepared. Branch polyglycolide copolymer improves the toughness and heat resistance of the material.

Benefits of technology

The obtained maleic anhydride grafted polyglycolide copolymer has high right-angle tear resistance strength, elongation at break and glass transition temperature, and is suitable for use in degradable medical surgical sutures, fracture fixtures and drug controlled release carriers. , material performance is significantly improved and easy to produce in industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264391A_ABST
    Figure CN119264391A_ABST
Patent Text Reader

Abstract

The invention provides a polyglycolide graft copolymer, which has a structure shown in the following general formula: R1, R2, R3, R4,..., Rn-3, Rn-2, Rn-1 and Rn are respectively and independently selected from H or # imgabs 0 #, two substituent groups connected to the same carbon atom are not # imgabs 1 # at the same time, and in R1, R2, R3, R4,..., Rn-3, Rn-2, Rn-1 and Rn, the mole percentage of the substituent group # imgabs 2 # is not less than 5%. The preparation method comprises the following steps: firstly, polymerizing maleic anhydride and glycolide to carry out graft modification to obtain MA-GA, and then carrying out low-temperature prepolymerization and high-temperature polymerization on MA-GA to obtain a high-molecular-weight copolymer. According to the invention, the grafting efficiency is greatly improved, the molecular weight of the polymer is increased, more maleic anhydride polar groups are successfully introduced to the side chain of the polyglycolide through the grafting reaction, and the toughness and elongation at break of the polyglycolide material are improved. # imgabs3 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to glycolide ring-opening polymerization technology, in particular to a high molecular weight polyglycolide graft copolymer and a preparation method thereof, and belongs to the field of polymer material synthesis. Background Art

[0002] Polyglycolide is a polymer material with good biocompatibility and biodegradability. Compared with traditional polymer materials, polyglycolide can be completely degraded in the human body without the participation of special enzymes, and the degradation products can be absorbed and metabolized by the body, eventually forming carbon dioxide and water. Due to its excellent biocompatibility and biodegradability, polyglycolide and its copolymers are widely used in degradable medical surgical sutures, fracture internal fixation, drug controlled release carriers and tissue engineering scaffolds.

[0003] There are two main methods for preparing polyglycolic acid. One is to obtain it through the polycondensation reaction of glycolic acid (the direct polycondensation method is generally the direct dehydration (dealcoholization) polycondensation of glycolic acid (ester)). This method does not require the preparation and purification of intermediate products such as dimers, which greatly reduces the reaction process, and the operation is relatively simple, requires fewer instruments and equipment, and does not require high monomer purity. However, the disadvantages are also obvious: since the equilibrium constant of the reaction is not large, and it is difficult to achieve a high degree of dehydration during the polymerization process, the molecular weight of the product is often low. The molecular weight of polyglycolide usually obtained by this method is only a few thousand, and the physical and chemical properties do not meet the requirements. Moreover, due to the easy decomposition of polyglycolide, its mechanical strength is far from meeting the requirements of fracture stent materials or surgical sutures. In addition, the melt polycondensation reaction often needs to be carried out at a higher temperature, and the product is easily oxidized by high temperature and causes discoloration. The other is to heat and decompose the glycolic acid polycondensation polymer to obtain cyclic glycolide, and use glycolide ring-opening polymerization to obtain high molecular weight polyglycolic acid with a molecular weight of tens of thousands to hundreds of thousands, which can meet the needs of post-processing. The ring-opening polymerization of glycolide generally occurs under relatively mild conditions and has some characteristics of active polymerization. Unlike conventional polycondensation reactions, it has fewer side reactions, does not have the problem of equal ratio of raw materials, and is easier to obtain products with higher molecular weight. At the same time, the ring-opening polymerization of glycolide requires a suitable catalyst to promote it, otherwise the relative molecular weight will be difficult to increase.

[0004] Polyglycolide has the disadvantages of being brittle, hydrophobic, and having low toughness. Therefore, it is difficult to directly prepare industrial products from polyglycolide materials like general-purpose plastics such as polyethylene and polypropylene, and it must be modified and processed. At present, the most commonly used method is to optimize its performance by blending polyglycolide with other plastics. Although this method is simple, it does not fundamentally change the properties of polyglycolide materials. In addition, some studies have improved the performance of materials by adding plasticizers or compatibilizers to polyglycolide materials. For example, maleic anhydride is a good compatibilizer. Maleic anhydride is a polar monomer material. Polyglycolide is modified by maleic anhydride to increase the polarity and toughness of polyglycolide materials. At present, the most commonly used method at home and abroad is to add maleic anhydride to polyglycolide or polyglycolide copolymers to improve the toughness of polyglycolide or polyglycolide copolymers, but the modification effect of this method is not obvious.

[0005] Chinese patent CN107840949A mixes a bifunctional end-capped polysiloxane oligomer with glycolide in the presence of an organic solvent, and copolymerizes under the action of a catalyst to obtain a polyglycolide-polysiloxane block copolymer, i.e., the organosilicon-modified polyglycolide. Compared with polyglycolide, the block copolymer has the characteristics of good flexibility, good impact resistance, and good heat resistance. It can be applied in the field of 3D printing technology, and can be quickly and efficiently made into complex structural parts for use in fields such as bioengineering. The toughness of polyglycolide is improved by copolymerization, but the molecular weight and strength of the polymer are small. Chinese patent CN102634001A uses benzyl chloride as an end-capping agent to perform an end-capping reaction on biodegradable polyester polyglycolide. The end-capped biodegradable polyglycolide has significantly improved hydrolysis resistance and thermal stability compared with the unend-capped modified polyglycolide, but only polar groups are connected to the end groups of polyglycolide, and the improvement effect is not significant. Chinese patent CN107488343A adds maleic anhydride to a blend of polyglycolide and other resins, and prepares a polyglycolide copolyester material by extrusion through a thermal reaction screw extruder. Maleic anhydride improves the compatibility between polyglycolide and other resins to a certain extent, but it is difficult to fundamentally change the thermodynamic properties of polyglycolide.

[0006] In summary, the current processes for the preparation and modification of polyglycolide have the following main problems: (1) The quality requirements for the glycolide monomer raw materials are high, and the free hydroxyl content (free acid and water) in the glycolide monomer seriously affects the degree of polymerization of polyglycolide. (2) Pure polyglycolide products have poor heat resistance and low toughness, and require modification and processing for industrial application. (3) Simply adding plasticizers and toughening agents to polyglycolide materials cannot fundamentally improve the thermodynamic properties of polyglycolide. (4) The grafting or esterification reaction on the side chain or end group of the polyglycolide macromolecular chain has low reaction activity and poor modification effect. Summary of the invention

[0007] In view of the above shortcomings, the present invention provides a polyglycolide graft copolymer and a preparation method thereof, which adopts a reaction route different from the prior art to prepare a maleic anhydride grafted polyglycolide copolymer material (MA-PGA) with a higher molecular weight. The maleic anhydride grafting rate is high, and the MA-PGA material has good toughness and heat resistance, is green and degradable, and is easy to industrialize.

[0008] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0009] The technical purpose of the first aspect of the present invention is to provide a polyglycolide graft copolymer, which is a compound having a general formula I structure:

[0010]

[0011] Among them, R1, R2, R3, R4, ..., R n-3 , R n-2 , R n-1 and R n are independently selected from H or The two substituents attached to the same carbon atom are not And R1, R2, R3, R4, ..., R n-3 , R n-2 , R n-1 and R n In the The molar percentage is not less than 5%, preferably 5%-50%, more preferably 10%-45%, most preferably 25%-40%.

[0012] Furthermore, the weight average molecular weight of the polyglycolide graft copolymer is 1.0×10 5 -3.5×10 5 , preferably 1.5×10 5 -3×10 5 .

[0013] Furthermore, the right-angle tear strength of the copolymer is not less than 250 kN / m, preferably 260-290 kN / m; the elongation at break is not less than 15%, preferably 18-30%, and the glass transition temperature is 60-70°C.

[0014] In the present invention, the right-angle tear strength and elongation at break are measured by a universal mechanical tester; the weight average molecular weight is measured by a gel chromatography method; and the glass transition temperature is measured by a differential scanning calorimeter method; which are described in detail below.

[0015] The technical purpose of the second aspect of the present invention is to provide a method for preparing a polyglycolide graft copolymer, comprising the following contents:

[0016] (1) mixing glycolide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted glycolide (MA-GA), and purifying the product;

[0017] (2) mixing the MA-GA obtained in (1) with a catalyst and an initiator, and prepolymerizing at low temperature to obtain a MA-GA oligomer;

[0018] (3) The MA-GA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA).

[0019] Furthermore, the initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, preferably dicumyl peroxide; and the amount of the initiator added is 0.1-5% by weight, preferably 0.5-2.0% by weight of glycolide.

[0020] Furthermore, step (1) is carried out at a constant temperature under an inert gas flow, preferably a nitrogen flow, and vacuum conditions, the reaction temperature is 50-150°C, preferably 80-120°C, the reaction pressure is 2-100kPa, preferably 20-60kPa; the reaction time is 0.5-10h, preferably 2-6h; the gas flow rate of the nitrogen flow protection is 0.5-6m / s, preferably 2-4m / s; based on the weight of glycolide, the maleic anhydride is 100-300% of glycolide, preferably 150-200%.

[0021] Furthermore, the optical purity of the glycolide in step (1) is 99.0-99.6%, preferably 99.4-99.6%, and purchased L-glycolide can be used.

[0022] The main reaction occurring in step (1) is shown below:

[0023]

[0024] Furthermore, the purification in step (1) is to remove glycolide that does not participate in the grafting reaction by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA). Specifically, the vacuum distillation temperature is 100-200°C, preferably 120-150°C; the pressure is 0-100 kPa, preferably 10-50 kPa; and the time is 1-10 h, preferably 2-6 h.

[0025] Furthermore, in step (2), the catalyst is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, preferably stannous octoate; and the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine, preferably triphenylphosphine.

[0026] Furthermore, in step (2), the amount of catalyst added is 0.1-5% by weight of MA-GA, preferably 0.5-3% by weight; the amount of initiator added is 0.05-5.0% by weight of MA-GA, preferably 0.5-2%.

[0027] Furthermore, step (2) is a low-temperature polymerization under an inert gas flow, preferably a nitrogen flow, and negative pressure conditions, the polymerization reaction temperature is 100-150°C, preferably 120-140°C; the reaction time is 2-15h, preferably 3-8h; the reaction pressure is 100-1000kPa, preferably 200-500kPa; the gas flow rate of the nitrogen flow is 0.5-6m / s, preferably 2-4m / s.

[0028] Furthermore, the antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, preferably triphenyl phosphite, and the amount of the antioxidant added is 0.1%-5%, preferably 1-3% by weight of the MA-GA oligomer.

[0029] Furthermore, the polymerization reaction temperature in step (3) is 150-250°C, preferably 160-200°C.

[0030] The main reaction process of steps (2) and (3) is shown below:

[0031]

[0032] Furthermore, step (3) uses a twin-screw extruder to realize the reaction process, adds MA-GA oligomer and antioxidant into the twin-screw extruder for polymerization reaction, and performs high-temperature reactive mixing and extrusion granulation to finally obtain maleic anhydride grafted polyglycolide copolymer material (MA-PGA).

[0033] The technical purpose of the third aspect of the present invention is to provide the application of polyglycolide graft copolymers, wherein the polyglycolide graft copolymers are applied to degradable medical surgical sutures, fracture internal fixators, drug controlled release carriers, and tissue engineering scaffolds.

[0034] Compared with the existing technology, the present invention has the following advantages:

[0035] (1) Compared with the prior art, the present invention provides a new route for synthesizing polyglycolide graft copolymers, wherein maleic anhydride (MA) and glycolide (GA) are first polymerized to obtain maleic anhydride-glycolide copolymers (MA-GA), and then MA-GA is prepolymerized at low temperature to obtain MA-GA oligomers, and finally MA-GA oligomers are polymerized at high temperature to obtain high molecular weight maleic anhydride grafted polyglycolide copolymers.

[0036] (2) The method of the present invention first carries out a grafting reaction of maleic anhydride before the polymerization of glycolide, which greatly improves the grafting efficiency and increases the molecular weight of the polymer. More maleic anhydride polar groups are successfully introduced into the side chains of polyglycolide through the grafting reaction, thereby improving the toughness and elongation at break of the polyglycolide material. By adopting the preparation method provided by the present invention, a graft copolymer with a grafting rate of 50% can be obtained in theory. By adjusting the raw material ratio, the content of the grafted group in the graft copolymer can be effectively adjusted, thereby adjusting the performance of the graft copolymer.

[0037] (3) Since a large amount of maleic anhydride ring structure is introduced into the side chain of polyglycolide, the glass transition temperature of the polyglycolide material is increased, and the prepared graft-modified polyglycolide copolymer material is green and fully biodegradable.

[0038] (4) The product of the present invention retains the terminal hydroxyl group of the graft copolymer, so that the graft copolymer can be further modified through the functional group to further control the properties of the copolymer.

[0039] (5) The bulk prepolymerization of glycolide is carried out in a reactor and coupled with a twin-screw extruder for copolymerization. The reaction operation is simple and easy to industrialize.

[0040] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0041] The following non-limiting examples can enable those of ordinary skill in the art to more fully understand the present invention, but do not limit the present invention in any way. The reagents, materials, and instruments involved in the following examples, unless otherwise specified, can all be obtained through regular commercial channels. The tests and inspection methods involved in the following examples, unless otherwise specified, are all existing tests and inspection methods in the prior art. The following examples provide a clear and complete description of the technical scheme of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All obvious changes or changes derived from the present invention still fall within the scope of protection of the present invention.

[0042] The following are the test methods for the performance parameters involved in the embodiments:

[0043] (1) Grafting rate of grafted groups:

[0044] The grafting rate of the grafted groups in the polylactic acid graft copolymer was determined by a chemical titration method, specifically: a certain mass of the polylactic acid graft copolymer was weighed and placed in a conical flask, a certain amount of tetrahydrofuran was added to dissolve it, and a small amount of thymol blue / DMF indicator was added dropwise; it was titrated with an excess of 0.05 mol / L potassium hydroxide ethanol solution, and back-titrated with 0.01 mol / L HCl-isopropanol solution.

[0045] Grafting rate = n2 / n1×100%, n1 = (m0-m2) / M1, n2 = m2 / M2, that is, grafting rate = [(0.05V KOH -0.01V HCl )×2×M1] / [m0-(0.05V KOH -0.01V HCl )×2×M2]; where m0 is the mass of the weighed polylactic acid graft copolymer, in g; m2 is the total mass of the grafted groups on the polylactic acid molecular chain, calculated based on the consumed KOH; n1 is the degree of polymerization of polylactic acid, i.e., the amount of substance of the lactic acid unit, n2 is the amount of substance of the grafted groups on the polylactic acid molecular chain, M1 is the molar mass of lactic acid, M2 is the molar mass of the grafted groups, V KOH V is the volume of potassium hydroxide ethanol solution added, in mL; HCl The volume of HCl-isopropanol solution consumed in titration, in mL.

[0046] (2) Right-angle tear strength and elongation at break: measured using a universal mechanical testing machine in accordance with GB / T1039-1992.

[0047] (3) Glass transition temperature: measured by differential scanning calorimeter (DSC) (DSC 204, NETZSCH, Germany). Test conditions: sample weight 5-10 mg, firstly, the sample was heated from room temperature to 200°C at a heating rate of 10°C / min, and kept isothermally for 5 min to eliminate the thermal history of the sample; then, the sample was quickly cooled to -20°C, and then heated from -20°C to 200°C at a heating rate of 10°C / min; nitrogen was introduced as protective gas during the entire test, and the flow rate of nitrogen was set to 50 mL / min.

[0048] (4) Polymer weight average molecular weight: measured by gel permeation chromatography (GPC) using gel permeation chromatography (GPC Waters 1515 system) to characterize the molecular weight of the polylactic acid graft copolymer sample. Chromatographically pure THF was used as the mobile phase, the flow rate was 1.0 ml / min, and the column temperature was 35°C. Before the test, the sample was dissolved in THF at a concentration of 5 mg / mL, filtered through a polytetrafluoroethylene (PTFE) filter membrane with a pore size of 0.22 μm, and then injected, and calibrated with a narrow distribution polystyrene (PS) standard.

[0049] (5) Detection of terminal hydroxyl groups: measured using the phthalic anhydride method in accordance with GB / T 12008.3-2009.

[0050] Example 1

[0051] (1) Add glycolide and maleic anhydride into a reaction kettle, add diisopropylbenzene peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain maleic anhydride grafted glycolide. The reaction temperature for grafting modification is 95°C, the reaction pressure is 35 kPa, the reaction time is 2 h, and the gas flow rate of the nitrogen flow protection is 2 m / s; based on the weight of glycolide, the maleic anhydride is 140% of the glycolide, and the diisopropylbenzene peroxide is 0.5% of the glycolide.

[0052] (2) removing the glycolide that does not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA); the vacuum distillation temperature is 125° C., the pressure is 15 kPa, and the time is 2 h.

[0053] (3) The maleic anhydride grafted glycolide (MA-GA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and under nitrogen flow and negative pressure conditions to obtain MA-GA oligomers; the reaction temperature of the low-temperature prepolymerization is 130° C., the reaction time is 3 h, the reaction pressure is 300 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and based on the weight of the maleic anhydride grafted glycolide (MA-GA), the catalyst stannous octoate is 0.5% of the MA-GA; the initiator triphenylphosphine is 0.2% of the MA-GA.

[0054] (4) adding the MA-GA oligomer of step (3) into a twin-screw extruder for polymerization reaction, adding an antioxidant at the same time, and performing reactive mixing and extrusion granulation at high temperature to finally obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA); based on the weight of the MA-GA oligomer, the antioxidant triphenyl phosphite is 0.5% of the MA-GA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.

[0055] Performance characterization: The right-angle tear strength of the maleic anhydride grafted polyglycolide copolymer material was measured to be 262KN / m, the elongation at break was 18%, the glass transition temperature was 63°C, and the molecular weight of the polymer was 1.82×10 5 The maleic anhydride grafting rate of the polymer was 28.9% as determined by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.

[0056] Example 2

[0057] (1) Add glycolide and maleic anhydride into a reaction kettle, add diisopropylbenzene peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain maleic anhydride grafted glycolide. The reaction temperature for grafting modification is 100°C, the reaction pressure is 35 kPa, the reaction time is 3 hours, and the gas flow rate of the nitrogen flow protection is 2.5 m / s; based on the weight of glycolide, the maleic anhydride is 145% of the glycolide, and the diisopropylbenzene peroxide is 0.6% of the glycolide.

[0058] (2) The glycolide that does not participate in the grafting reaction in step (1) is removed by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA); the vacuum distillation temperature is 130° C.; the pressure is 15 kPa, and the time is 2.5 h.

[0059] (3) The maleic anhydride grafted glycolide (MA-GA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and nitrogen flow and negative pressure conditions to obtain MA-GA oligomers; the reaction temperature of the low-temperature prepolymerization is 135° C., the reaction time is 4 hours, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and the catalyst stannous octoate is 0.6% of the weight of the maleic anhydride grafted glycolide (MA-GA); the initiator triphenylphosphine is 0.25% of the MA-GA.

[0060] (4) adding the MA-GA oligomer of step (3) into a twin-screw extruder for polymerization reaction, adding an antioxidant at the same time, and subjecting to high-temperature reactive mixing and extrusion granulation, to finally obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA); based on the weight of the MA-GA oligomer, the antioxidant triphenyl phosphite is 0.6% of the MA-GA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.

[0061] Performance characterization: The right-angle tear strength of the maleic anhydride grafted polyglycolide copolymer material was measured to be 270 KN / m, the elongation at break was 21%, the glass transition temperature was 65°C, and the molecular weight of the polymer was 2.05×10 5 The maleic anhydride grafting rate of the polymer was 31.5% by chemical titration method. The presence of terminal hydroxyl groups was determined by chemical titration method.

[0062] Example 3

[0063] (1) Add glycolide and maleic anhydride into a reaction kettle, add diisopropylbenzene peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain maleic anhydride grafted glycolide. The reaction temperature for grafting modification is 100°C, the reaction pressure is 40 kPa, the reaction time is 3 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of glycolide, the maleic anhydride is 150% of the glycolide, and the diisopropylbenzene peroxide is 0.65% of the glycolide.

[0064] (2) The glycolide that does not participate in the grafting reaction in step (1) is removed by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA); the vacuum distillation temperature is 130° C.; the pressure is 20 kPa, and the time is 3 h.

[0065] (3) The maleic anhydride grafted glycolide (MA-GA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and nitrogen flow and negative pressure conditions to obtain MA-GA oligomers; the reaction temperature of the low-temperature prepolymerization is 135° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and the catalyst stannous octoate is 0.65% of the weight of the maleic anhydride grafted glycolide (MA-GA); the initiator triphenylphosphine is 0.3% of the weight of the MA-GA.

[0066] (4) adding the MA-GA oligomer of step (3) into a twin-screw extruder for polymerization reaction, adding an antioxidant, and performing high-temperature reactive mixing and extrusion granulation to finally obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA); based on the weight of the MA-GA oligomer, the antioxidant triphenyl phosphite is 0.6% of the MA-GA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 185°C.

[0067] Performance characterization: The right-angle tear strength of the maleic anhydride grafted polyglycolide copolymer material was measured to be 278KN / m, the elongation at break was 23%, the glass transition temperature was 68°C, and the molecular weight of the polymer was 2.26×10 5 The maleic anhydride grafting rate of the polymer was 35.7% by chemical titration method. The presence of terminal hydroxyl groups was determined by chemical titration method.

[0068] Example 4

[0069] (1) Add glycolide and maleic anhydride into a reaction kettle, add diisopropylbenzene peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain maleic anhydride grafted glycolide. The reaction temperature for grafting modification is 105°C, the reaction pressure is 45 kPa, the reaction time is 3.5 h, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of glycolide, the maleic anhydride is 155% of the glycolide, and the diisopropylbenzene peroxide is 0.7% of the glycolide.

[0070] (2) The glycolide that does not participate in the grafting reaction in step (1) is removed by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA); the vacuum distillation temperature is 130° C.; the pressure is 25 kPa, and the time is 3.5 h.

[0071] (3) The maleic anhydride grafted glycolide (MA-GA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and nitrogen flow and negative pressure conditions to obtain MA-GA oligomers; the reaction temperature of the low-temperature prepolymerization is 140° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and based on the weight of the maleic anhydride grafted glycolide (MA-GA), the catalyst stannous octoate is 0.75% of MA-GA; the initiator triphenylphosphine is 0.35% of MA-GA.

[0072] (4) adding the MA-GA oligomer of step (3) into a twin-screw extruder for polymerization reaction, adding an antioxidant at the same time, and subjecting the mixture to high-temperature reactive mixing, extrusion and granulation to obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA); based on the weight of the MA-GA oligomer, the antioxidant triphenyl phosphite is 0.65% of the MA-GA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing, extrusion and granulation is 185°C.

[0073] Performance characterization: The right-angle tear strength of the maleic anhydride grafted polyglycolide copolymer material was measured to be 286 KN / m, the elongation at break was 26%, the glass transition temperature was 69°C, and the molecular weight of the polymer was 2.51×10 5 The maleic anhydride grafting rate of the polymer was 38.2% by chemical titration method. The presence of terminal hydroxyl groups was determined by chemical titration method.

[0074] Example 5

[0075] (1) Add glycolide and maleic anhydride into a reaction kettle, add diisopropylbenzene peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain maleic anhydride grafted glycolide. The reaction temperature for grafting modification is 110°C, the reaction pressure is 55 kPa, the reaction time is 4 hours, and the gas flow rate of the nitrogen flow protection is 4 m / s; based on the weight of glycolide, the maleic anhydride is 160% of the glycolide, and the diisopropylbenzene peroxide is 0.8% of the glycolide.

[0076] (2) The glycolide that does not participate in the grafting reaction in step (1) is removed by vacuum distillation to obtain purified maleic anhydride grafted glycolide (MA-GA); the vacuum distillation temperature is 135° C.; the pressure is 30 kPa, and the time is 3.5 h.

[0077] (3) The maleic anhydride grafted glycolide (MA-GA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and under nitrogen flow and negative pressure conditions to obtain a MA-GA oligomer; the reaction temperature of the low-temperature prepolymerization is 140° C., the reaction time is 5 h, the reaction pressure is 400 kPa, the gas flow rate of the nitrogen flow protection is 4 m / s, and based on the weight of the maleic anhydride grafted glycolide (MA-GA), the catalyst stannous octoate is 0.8% of the MA-GA; the initiator triphenylphosphine is 0.4% of the MA-GA.

[0078] (4) adding the MA-GA oligomer of step (3) into a twin-screw extruder for polymerization reaction, adding an antioxidant at the same time, and subjecting to high-temperature reactive mixing and extrusion granulation, to finally obtain a maleic anhydride grafted polyglycolide copolymer material (MA-PGA); based on the weight of the MA-GA oligomer, the antioxidant triphenyl phosphite is 0.7% of the MA-GA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 190°C.

[0079] Performance characterization: The right-angle tear strength of the maleic anhydride grafted polyglycolide copolymer material was measured to be 272 KN / m, the elongation at break was 21.6%, the glass transition temperature was 66.5°C, and the molecular weight of the polymer was 2.11×10 5 The maleic anhydride grafting rate of the polymer was 32.3% by chemical titration method. The presence of terminal hydroxyl groups was determined by chemical titration method.

[0080] Comparative Example 1

[0081] The copolymer is prepared by first polymerizing glycolide and then grafting it:

[0082] (1) Glycolide is prepolymerized at low temperature under the action of a catalyst and an initiator, and under nitrogen flow and negative pressure to obtain an oligomer. The reaction temperature of the low temperature prepolymerization is 130° C., the reaction time is 3 hours, the reaction pressure is 300 kPa, the flow rate of the nitrogen flow is 3 m / s, and the amount of the catalyst stannous octoate added is 0.5 wt% of the amount of glycolide used; the amount of the initiator triphenylphosphine added is 0.2 wt% of the amount of glycolide used.

[0083] (2) adding the oligomer obtained in step (1) into a twin-screw extruder for polymerization reaction, adding maleic anhydride and an antioxidant at the same time, and subjecting the mixture to high-temperature reactive mixing, extrusion and granulation to obtain a grafted polymer; based on the weight of the oligomer, the amount of maleic anhydride added is 15 wt% of the amount of the oligomer (and the inventors have experimentally verified that even if the amount of maleic anhydride added is further increased, the grafting rate is not improved), the amount of the antioxidant triphenyl phosphite added is 0.5 wt% of the amount of the oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing, extrusion and granulation is 180°C.

[0084] Product performance: The right-angle tear strength of the copolymer material was measured to be 182KN / m, the elongation at break was 9%, the glass transition temperature was 48°C, and the molecular weight of the polymer was 1.68×10 5 The maleic anhydride grafting rate of the polymer was determined to be 1.3% by chemical titration method; the presence of terminal hydroxyl groups could not be detected by chemical titration method.

Claims

1. A polyglycolide graft copolymer, characterized in that: It is a compound having the general structure of formula I: Among them, R1, R2, R3, R4, ..., R n-3 , R n-2 , R n-1 and R n are independently selected from H or The two substituents attached to the same carbon atom are not And R1, R2, R3, R4, ..., R n-3 , R n-2 , R n-1 and R n In the The molar percentage is not less than 5%, preferably 5%-50%, more preferably 10%-45%, most preferably 25%-40%.

2. The copolymer according to claim 1, characterized in that Its weight average molecular weight is 1.0×10 5 -3.5×10 5 .

3. The copolymer according to claim 1, characterized in that Its right-angle tearing strength is not less than 250kN / m, its elongation at break is not less than 15%, and its glass transition temperature is 60-70°C.

4. The method for preparing the polyglycolide graft copolymer according to claim 1, comprising the following contents: (1) mixing glycolide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted glycolide MA-GA, and purifying the product; (2) mixing the MA-GA obtained in (1) with a catalyst and an initiator, and prepolymerizing at low temperature to obtain a MA-GA oligomer; (3) The MA-GA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain a maleic anhydride grafted polyglycolide copolymer material MA-PGA.

5. The preparation method according to claim 4, characterized in that: The initiator in step (1) is diisopropylbenzene peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the amount of the initiator added is 0.1-5% by weight of glycolide.

6. The preparation method according to claim 4, characterized in that: Step (1) is a constant temperature reaction under inert gas flow and vacuum conditions, the reaction temperature is 50-150° C., the reaction pressure is 2-100 kPa, and the reaction time is 1-20 h.

7. The preparation method according to claim 4, characterized in that: The amount of maleic anhydride added is 100-300% of the weight of glycolide.

8. The preparation method according to claim 4, characterized in that: In step (2), the catalyst is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride; and the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine.

9. The preparation method according to claim 4, characterized in that: In step (2), the amount of the catalyst added is 0.1-5% of the MA-GA, and the amount of the initiator added is 0.05-5.0% of the MA-GA.

10. The preparation method according to claim 4, characterized in that: Step (2) is low-temperature polymerization under inert gas flow and negative pressure conditions, the polymerization reaction temperature is 100-150° C., the reaction time is 2-15 hours, and the reaction pressure is 100-1000 kPa.

11. The preparation method according to claim 4, characterized in that: The antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, and the amount of the antioxidant added is 0.1%-5% by weight of the MA-GA oligomer.

12. The preparation method according to claim 4, characterized in that: The temperature of the polymerization reaction in step (3) is 150-250°C.

13. The preparation method according to claim 4, characterized in that: Step (3) uses a twin-screw extruder to achieve the reaction process.

14. Use of the polyglycolide graft copolymer according to claim 1, wherein the copolymer is used in the fields of degradable medical surgical sutures, fracture internal fixators, drug controlled release carriers and tissue engineering scaffolds.

Citation Information

Patent Citations

  • Method for enhancing hydrolysis resistance of biodegradable copolyester by way of blocking

    CN102634001A

  • High-barrier completely-biodegradable mulching film and preparation method thereof

    CN107488343A

  • Preparation method of organic silicone modified polyglycollide

    CN107840949A

  • Preparation method for maleic anhydride-modified polylactic-co-glycolic acid

    CN103570884A

  • Technology for preparing high-molecular-weight MPLGA by directly grafting maleic anhydride onto PLGA

    CN105315412A